Обнаружение текста на изображениях с неоднородным фоном с помощью алгоритма stroke width transform - Сергеев, Я. С. (ХНУРЕ, 2019)
This paper proposes a solution to the text characters detection and symbols extraction problem in images with a non-uniform background using the SWT algorithm. This method allows to recognize and select characters with an accuracy of 85%, regardless of size, font family and language